2015
DOI: 10.2215/cjn.11931214
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Marine n-3 Polyunsaturated Fatty Acid Levels and Survival after Renal Transplantation

Abstract: Background and objectives Several studies have reported beneficial cardiovascular effects of marine n-3 polyunsaturated fatty acids. To date, no large studies have investigated the potential benefits of marine n-3 polyunsaturated fatty acids in recipients of renal transplants.Design, setting, participants, & measurements In this observational cohort study of 1990 Norwegian recipients of renal transplants transplanted between 1999 and 2011, associations between marine n-3 polyunsaturated fatty acid levels and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
53
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 52 publications
5
53
0
Order By: Relevance
“…5,[12][13][14][15] A recent randomized clinical trial (RCT) in myocardial infarction survivors reported less development of myocardial fibrosis in patients who received high-dose marine n-3 FA supplements. 17,18 In that observational cohort, plasma marine n-3 FA levels were inversely associated with plasma creatinine, inflammatory biomarkers and triglycerides, acute rejections beyond the early posttransplant phase, and development of interstitial fibrosis (IF) during the first year after transplantation. 17,18 In that observational cohort, plasma marine n-3 FA levels were inversely associated with plasma creatinine, inflammatory biomarkers and triglycerides, acute rejections beyond the early posttransplant phase, and development of interstitial fibrosis (IF) during the first year after transplantation.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…5,[12][13][14][15] A recent randomized clinical trial (RCT) in myocardial infarction survivors reported less development of myocardial fibrosis in patients who received high-dose marine n-3 FA supplements. 17,18 In that observational cohort, plasma marine n-3 FA levels were inversely associated with plasma creatinine, inflammatory biomarkers and triglycerides, acute rejections beyond the early posttransplant phase, and development of interstitial fibrosis (IF) during the first year after transplantation. 17,18 In that observational cohort, plasma marine n-3 FA levels were inversely associated with plasma creatinine, inflammatory biomarkers and triglycerides, acute rejections beyond the early posttransplant phase, and development of interstitial fibrosis (IF) during the first year after transplantation.…”
Section: Introductionmentioning
confidence: 91%
“…17,18 In that observational cohort, plasma marine n-3 FA levels were inversely associated with plasma creatinine, inflammatory biomarkers and triglycerides, acute rejections beyond the early posttransplant phase, and development of interstitial fibrosis (IF) during the first year after transplantation. [17][18][19][20][21] The present study is the largest RCT investigating the effects of marine n-3 FA supplementation in renal transplantation performed to date, and the first to include data on renal graft histopathological indices and endothelial function. The main objective of this trial was to evaluate whether daily supplementation of 2.6 g marine n-3 FAs for 44 weeks, compared with controls, would improve renal function beyond standard care in renal transplant recipients.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations